x+6t+5=

Simple and best practice solution for x+6t+5= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+6t+5= equation:


Simplifying
x + 6t + 5 = 0

Reorder the terms:
5 + 6t + x = 0

Solving
5 + 6t + x = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + 6t + -5 + x = 0 + -5

Reorder the terms:
5 + -5 + 6t + x = 0 + -5

Combine like terms: 5 + -5 = 0
0 + 6t + x = 0 + -5
6t + x = 0 + -5

Combine like terms: 0 + -5 = -5
6t + x = -5

Add '-1x' to each side of the equation.
6t + x + -1x = -5 + -1x

Combine like terms: x + -1x = 0
6t + 0 = -5 + -1x
6t = -5 + -1x

Divide each side by '6'.
t = -0.8333333333 + -0.1666666667x

Simplifying
t = -0.8333333333 + -0.1666666667x

See similar equations:

| 3(x+11)=7x+5 | | 6(2-3n)=6n | | 6c-20=40 | | x^2-2(n-3)x+4n=0 | | 1.6-d=12.8 | | -9=5(y-6)-8y | | 10-2q=5+0.5q | | -3(2x-6)=-6x-18 | | =9a^6*a^9 | | 5(8x-2)=-130 | | 1. 2x-34=-20 | | 2x-27=x+13 | | -4x+6(x+3)=6 | | 21yd=ft | | (4b-5)*(2b+7)= | | 2(20+x)=5x+4 | | 3(r+2)=6r-5 | | x+(x-48)+3(x-48)=898 | | -19=-3v+7(v-5) | | x^2-(m+7)x+25=0 | | 22-6x=-26 | | 3*36= | | 16-8*4/8-1= | | 2(4*2)-64= | | 9-5n=12-1(6n+7) | | 6a-2a^2+2=0 | | v//46=34/23 | | 2(4s+4)=104 | | 196-25+5*8+2= | | 7z+9=4 | | 16+6+3(3-6)= | | 8x+2y=26 |

Equations solver categories